PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN AKIDAH AKHLAK DI MAN FAKFAK KABUPATEN FAKFAK PROVINSI PAPUA BARAT - Risna (Pascasarjana IAIN Sorong, 2025)
This is a study with the objectives: 1). to analyze the influence of the Independent Curriculum on students' learning interests in Faith and Morals Subject in class X MAN Fakfak 2). to analyze the influence of the Independent Curriculum on student learning outcomes in Faith and Morals Subject in class X MAN Fakfak. 3). to identify inhibiting and supporting factors of the implementation of the Independent Curriculum on students' interests and learning outcomes in Faith and Morals Subject in class X MAN Fakfak.The research method used is a quantitative method.The results of the study showed that: 1) Students' interest in learning Akidah Akhlak taught with the implementation of the Independent Curriculum in Class X A MAN Fakfak was in the very high category 2) Students' learning outcomes in learning Faith and Morals Subject taught with the implementation of the Independent Curriculum in class X A MAN Fakfak were in the very high category. 3). The supporting factors for the influence of the implementation of the Independent Curriculum on students' interest and learning outcomes in learning Faith and Morals Subject in Class X MAN Fakfak, namely the existence of KMA 347 of 2022 and Akidah Akhlak teachers participating in training on the implementation of the Independent Curriculum independently. Furthermore, the inhibiting factors for the influence of the implementation of the Independent Curriculum on students' interest and learning outcomes in learning Faith and Morals Subject in Class X MAN Fakfak, namely problems related to teachers, the madrasah ecosystem, and students.